HUBUNGAN ANTARA DURASI TIDUR DENGAN OBESITAS SENTRAL PADA REMAJA LAKI-LAKI - Nataxia, Caitlin; Dwi Primayanti, I Dewa Ayu Inten; Dinata, I Made Krisna; Adiatmika, I Putu Gede (Essence of Scientific Medical Journal; Vol 22 No 2 (2025): Volume 22 No. 2 (November 2024 - Maret 2025) Essential: Essence of Scientific Medical JournalDO - 10.24843/essential.v22i2.121217, 2025)
Sleep is an important element in a person's life as it plays a role in the regulation of food intake. Inadequate sleep duration, which is increasing among adolescent boys, can lead to conditions that increase appetite, leading to the incidence of central obesity. The purpose of this study was to determine the relationship between sleep duration and central obesity in adolescent boys. This study is categories in non-experimental analytical research with data collection using the cross-sectional method. Respondents in the study were students of a public high school in Denpasar who were still actively participating in school activities. Data on physical activity levels were obtained using the IPAQ-SF questionnaire which was distributed online to respondents. Central obesity data was obtained by measuring abdominal circumference. Research data from 96 respondents showed that respondents with sleep duration less than 8 hours (66.7%) were more than those with sleep duration >=8 hours (33.3%). A total of 39.6% of respondents did not have central obesity. Based on the results of bivariate analysis of the two variables, the p value = 0.003 was obtained, which stated that the research hypothesis was accepted. Based on the results of the study it can be concluded that there is a relationship between sleep duration and central obesity in adolescent boys. Sleep affects the incidence of central obesity through the production of hormones that regulate food intake. Key words: adolescent boy, central obesity, sleep duration